TIGAR deficiency sensitizes angiotensin‐II‐induced renal fibrosis and glomerular injury. Issue 8 (20th April 2022) - He, Xiaochen; Cantrell, Aubrey C.; Williams, Quinesha A.; Chen, Jian‐Xiong; Zeng, Heng
Abstract: Angiotensin II (Ang‐II) is one of the major contributors to the progression of renal fibrosis, inflammation, glomerular injury, and chronic kidney disease. Emerging evidence suggests that renal glycolysis plays an important role in renal fibrosis and injury. TP53‐induced glycolysis and apoptosis regulator (TIGAR) has been shown to regulate glycolysis. In the present study, we investigated the role of TIGAR in renal glycolysis, fibrosis, and glomerular injury during Ang‐II‐induced hypertension. Wild‐type (WT) and TIGAR knockout (KO) mice were infused with Ang‐II (1 µg/kg/min) via mini‐pumps for 4 weeks. The mean arterial pressure was similar between the WT and TIGAR KO mice, associated with a comparable increase in plasma creatinine level. Ang‐II infusion resulted in a significant increase in renal interstitial fibrosis and more mesangial expansion and collapsed glomerular structure in the TIGAR KO mice. These were associated with elevated expression of hypoxia‐inducible factor‐1 alpha, glycolytic enzymes, and transforming growth factor beta 1 in the TIGAR KO mice after Ang‐II infusion when compared to that of the WT mice. The coupled‐enzyme method revealed that PFK‐1 activity was similarly increased in WT and TIGAR KO mice after Ang‐II infusion. Our present study suggests that TIGAR is involved in Ang‐II‐induced renal fibrosis and glomerular injury, although it has little effect on blood pressure and renal function. Knockout of TIGAR sensitizes Ang‐II‐induced renal fibrosis and injury. This study provides new insights into the role of TIGAR in renal metabolism and pathological remodeling during Ang‐II‐induced hypertension. Abstract : Knockout of TIGAR sensitizes Ang II‐mediated HIF‐1α and TGF‐β expression in the mouse kidney. Knockout of TIGAR enhances Ang‐II‐induced increase in renal interstitial fibrosis as well as more mesangial expansion and collapsed capillaries. This study provides new insights into the role of TIGAR in renal metabolism and pathological remodeling during Ang‐II‐induced hypertension.